Antiplatelet vs. Anticoagulation in Cervical Artery Dissection: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Liu, Sihua; Zhang, Xiao; Bai, Xuesong; Yang, Yutong; Wang, Tao; Xu, Xin; Xu, Ran; Li, Long; Feng, Yao; Yang, Kun; Wang, Xue; Guo, Xiaofan; et al. (Frontiers in Neurology, 2021)
Objective: The optimal management for cervical artery dissection (CAD) is uncertain. This study aims to summarize current randomized controlled trials (RCTs) to compare the efficacy and safety of antiplatelet and anticoagulation therapies for CAD. Methods: A literature search was conducted in major databases, including MEDLINE, Embase, and the Cochrane Library. Only RCTs comparing antiplatelet and anticoagulation therapies for CAD patients were included. Combined estimates of the relative risk (RR) of antiplatelet versus anticoagulation were analyzed. Heterogeneity was measured using the I2 statistical analysis. Analyses were performed in the intention-to-treat (ITT) and per-protocol (PP) population, respectively. Results: Two RCTs involving 444 patients in the ITT population and 370 patients in the PP population were included. The quality of studies was high overall. In the ITT population, compared with patients in the anticoagulation group, patients in the antiplatelet group showed a higher rate of ischemic stroke within 3 months (RR = 6.73 [95% CI, 1.22–37.15], I2 = 0%, P = 0.029). No difference between these two treatment groups was found for the outcomes of transient ischemic attack (RR = 0.37 [95% CI, 0.09–1.58], I2 = 0%, P = 0.181), intracranial hemorrhage (RR = 0.33 [95% CI, 0.01–7.98], I2 = 0%, P = 0.494), major extracranial bleeding (RR = 0.31 [95% CI, 0.01–7.60], I2 = 0%, P = 0.476), or the composite of these outcomes within 3 months. For the PP population, the results of the meta-analysis of outcomes between antiplatelet and anticoagulation groups were consistent with the ITT population. Conclusions: Compared with antiplatelet, anticoagulation has a lower risk of ischemic stroke without increasing bleeding risk when treating CAD. Anticoagulation seems to be superior over antiplatelet in treating CAD but needs to be further tested by specifying many issues, such as location, initial symptom types, and treatment protocols.